The Effect Of Advertising Attractiveness, Influencer Marketing, And Online Customer Review On Smartphone Purchasing Decisions For Generation Z In Surabaya - Mahesa Hamisena; Christina Sudyasjayanti (UNIVED Press, 2024)
The usage of smartphones in Indonesia has continuously increased. In 2018, 56.2% of the Indonesian population used smartphones. One of the prominent market leaders is Samsung smartphones, which rank second with the largest market share in Indonesia at 20.99%. Indonesia is predominantly comprised of generation Z, accounting for approximately 27.94% of the total population. The role of digital marketing is highly significant in the decision-making process for smartphone purchases among generation Z. This study aims to determine the influence of Advertising Attractiveness, Influencer Marketing, and Online Customer Review on the purchasing decisions of smartphones by generation Z in Surabaya. This research uses a quantitative research approach. The study population consists of generation Z in Surabaya. The sampling technique employed is purposive sampling. The sample criteria include generation Z aged 15-29 years in Surabaya who have purchased a Samsung smartphone at least once, with a total sample size of 315 respondents. Data collection was conducted by distributing questionnaires to respondents through Google Forms. The research method involves multiple linear regression analysis using the SPSS program. The research results indicate that the significance value for all variables is 0.000 (< 0.05), leading to the conclusion that Advertising Attractiveness, Influencer Marketing, and Online Customer Review have a positive and significant influence on the smartphones purchasing decisions by generation Z in Surabaya.